Historical categories and the praxis of ethnicity in Ancient Israel - Nestor, Dermot A. (Trinity College (Dublin, Ireland). Department of Religions and Theology, 2003)
Within biblical archaeology the interpretation of ethnic groups has traditionally taken place within a narrative framework derived almost entirely from certain highly prized written sources, thereby reflecting the privileged status traditionally accorded to the written word over and above material culture in the study of historical periods. Such 'historical determinism' it is argued, frequently results in the circular, self-referential use of archaeological and documentary evidence, and an all too eager conflation of the material record with monolithic 'ethnic categories' extracted from historical sources.
Keywords: Hebrew Biblical and Theological Studies, Ph.D.; Ph.D. Trinity College Dublin